Harmonisasi Hukum Konstitusi dan Hukum Islam dalam Perlindungan Warisan Budaya Papua di Tengah Pembangunan Infrastruktur: Studi Kasus Situs Batu Peradaban Aitumeiri - Enny Martha Sasea; Marwati Riza; Syamsul Bachri; Ahmad Masum; Maskun Maskun (Syariah: Jurnal Hukum dan Pemikiran, 2025)
Rapid infrastructure development in Papua has intensified tension between economic growth and the protection of indigenous cultural heritage. This condition represents a critical phenomenon marked by regulatory change and the urgent need for sustainable legal solutions in culturally sensitive regions. Existing legal frameworks often operate in a fragmented manner, weakening effective heritage protection. The theoretical framework of this study lies at the intersection of constitutional law, Islamic law, and legal pluralism. Although the Indonesian Constitution guarantees cultural advancement and the recognition of indigenous rights, and Islamic law provides ethical guidance through maqÄá¹£id al-sharÄ«Ê¿ah, their integration in heritage governance remains limited. This study aims to examine the harmonization of constitutional law and Islamic law in protecting Papuaâ€™s cultural heritage, using the Aitumeiri Civilization Stone Site as a case study. The research employs a normative legal method with statutory and conceptual approaches, supported by qualitative analysis and a maqÄá¹£id al-sharÄ«Ê¿ah framework focusing on the protection of religion, intellect, and lineage. The findings reveal overlapping regulations, weak intergovernmental coordination, and limited indigenous participation as major obstacles to effective heritage governance. Integrating maqÄá¹£id al-sharÄ«Ê¿ah into constitutional interpretation strengthens normative coherence and moral legitimacy. In conclusion, harmonized and inclusive legal frameworks are essential to safeguard Papuaâ€™s cultural heritage within sustainable development. The study recommends strengthening maqÄá¹£id-based regional regulations, institutionalizing consultative mechanisms inspired by shÅ«rÄ, and mandating heritage impact assessments involving indigenous communities.